2014
DOI: 10.1517/13543784.2014.918953
|View full text |Cite
|
Sign up to set email alerts
|

Drugs targeting nitric oxide synthase for migraine treatment

Abstract: The data highlighted herein, from four placebo-controlled trials and 1 open-labeled clinical trial using 4 different NOS inhibitors on a total of 705 patients, provide convincing efficacy data only for the nonselective NOS inhibitor L-NMMA. Unfortunately, this NOS inhibitor raises cardiovascular safety concerns and has an unfavorable pharmacokinetic profile. As experimental studies predicted, iNOS inhibitors are ineffective in migraine. Still, upcoming selective nNOS inhibitors are a hope for migraine treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 61 publications
0
26
0
1
Order By: Relevance
“…The increased activity of central terminals of sensitized TG afferents can promote the upregulation of neuronal NOS (nNOS) in the postsynaptic neurons, which can both sensitize the second‐order neurons as well as the primary afferent terminals by retrograde diffusion of NO . Moreover, both NO and CGRP activate astrocytes and microglia .…”
Section: Role Of Trigeminal Cgrp In Migraine – Preclinical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…The increased activity of central terminals of sensitized TG afferents can promote the upregulation of neuronal NOS (nNOS) in the postsynaptic neurons, which can both sensitize the second‐order neurons as well as the primary afferent terminals by retrograde diffusion of NO . Moreover, both NO and CGRP activate astrocytes and microglia .…”
Section: Role Of Trigeminal Cgrp In Migraine – Preclinical Evidencementioning
confidence: 99%
“…[156][157][158][159][160] In the TG, CGRP secreted from neurons can activate signaling cascades by interacting with the CGRP receptors present on satellite glia and on adjacent non-CGRPergic TG neurons, inducing NO production in these glia and neurons to cause release of additional CGRP and the activation of signaling cascades to increase production of proinflammatory mediators, thus sensitizing TG neurons. [161][162][163] Studies performed with primary TG cultures suggested the presence of a feed-forward loop that can increase both CGRP and NO production (Fig. 2).…”
Section: Role Of Trigeminal Cgrp In Migraine -Preclinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…have prevented their therapeutic use. [39][40][41] For instance, efforts are still in progress to improve the permeability of nNOS inhibitors. [42][43][44] Therefore, developing a clinically useful NOS inhibitor remains a strong challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, another critical target for the inflammation suppressive activity regulated by andrographolide is the NO/inducible NOS (iNOS) pathway (Lim et al, 2012). The NO/iNOS system is involved in pain transmission, hyperalgesia, chronic pain, neuroinflammation and central sensitization (Barbanti et al, 2014). Despite the potent anti-inflammatory properties exhibited by AP, its anti-nociceptive and analgesic effects are still largely unexplored.…”
Section: Introductionmentioning
confidence: 99%